Leading the e-volution. - Isaacs, Lindsay (American City & County, 2008)
The article focuses on the computer system in Lakeland, Florida. According to a November 1968 article in "The American City," Lakeland started electronic data processing in 1964 and, for $3,900 monthly, leased a Burroughs B283 computer system that it used primarily to process bills for its utility customers. A list of the servers, workstations and laptops, networked printers and large-scale plotters owned by the city is presented. The city also owns more than 280 miles of fiber optics, and is migrating to a Voice over Internet Protocol telephone system.